УПРАВЛІННЯ ДЕРЖАВНИМИ ФІНАНСАМИ В УКРАЇНІ: ПРОБЛЕМИ І ШЛЯХИ ЇХ ВИРІШЕННЯ (Світ фінансів, 2017)
Петленко Ю. В., Котовський Т. А. Управління державними фінансами в Україні: проблеми і шляхи їх вирішення. Висвітлено актуальні проблеми управління державними фінансами в Україні, визначено ступінь їх впливу на економічне зростання країни та добробут суспільства. Розглянуто шляхи вирішення проблем управління державними фінансами, що полягають у імплементації нової моделі державного управління, яка являє собою перенесення основних практик, принципів і процесів управління фінансами в бізнес-середовищі до сфери державного управління з урахуванням його специфіки, а також визначено ефект від її реалізації на базі макроекономічної моделі Бруно-Фішера. Петленко Ю. В., Котовский Т. А. Управление государственными финансами в Украине: проблемы и пути их решения. Освещены актуальные проблемы управления государственными финансами в Украине, определена степень их влияния на рост экономики страны и благосостояние общества. Рассмотрены пути решения проблем управления государственными финансами, заключающиеся в имплементации новой модели государственного управления, которая представляет собой перенос основных практик, принципов и процессов управления финансами в бизнес-среде в сферу государственного управления с учетом его специфики, а также определен эффект от ее реализации на базе макроэкономической модели Бруно-Фишера. Petlenko Yu., Kotovskyi T. Public finance management in Ukraine: problems and solutions.Introduction. Building an effective and fair system of public finance is an important stimulus for the dynamic development of economy of Ukraine. In this case, balance and rationality of financial resources of Ukraine will contribute to creating an enabling macroeconomic environment for business and investment growth and provide guaranteed stability in the system of social protection. However, imbalances and problems in public finances are able to form a threat to national economic development. According to this the article is devoted to coverage of topical issues of public financial management in Ukraine and defining their solutions via the implementation of a new model of government – the transfer of key business practices in public administration.Results. Main solution for issues in a public finance management should be the implementation of the new government model which is based on using main principles of corporate finance management in public area. New government model includes elastic system of compensation to public officers which is based on KPIs, decentralization of budget system and controlling by independent auditor.Conclusion. The implementation of a new model of public administration requires systematic and deep reforms, which required considerable significant time and financial resources.